ANALYSIS OF THE COMPETENCY OF FRESH GRADUATED HIGHER EDUCATION IN SUPPORTING INDUSTRIAL ERA 4.0 - Edy Sahputra Sitepu; Agus Edy Rangkuti; Ferry Fachrizal (IJIET (International Journal of Indonesian Education and Teaching), 2020)
This article analyzes the need for Industry 4.0 HR competencies. The study was conducted at a number of tertiary institutions in Medan, where the sample was determined by purposive random sampling. The variables used in this study include; a) sense-making, b) social intelligent, c) novel and adaptive thinking, d) cross-cultural competency, e) computational thinking, f) new-media literacy, g) transdisciplinarity, h) design thinking, i) cognitive load management, j) virtual collaboration. Furthermore, the data were analyzed using the Confirmatory Factor Analysis approach. The output of this research is expected to provide input and strategies for universities in strengthening the quality of the fresh graduated HR output produced. The results of this study indicate that based on the results of Confirmatory Factor Analysis, the 10 variables used have a positive relationship between variables and can be an estimator to see how fresh graduated human resources are ready to face industry 4.0.DOI: 10.24071/ijiet.2020.040107